Geothermal waters of East-Ciscausasian artesian basin: economical aspects of using by the example of Khankala deposit - Anvar Mansurovich Farkhutdinov; Ildar Shamilevich Khamitov; Sergei Vladimirovich Cherkasov; Magomed Shavalovich Mintsaev; Sharputdi Shamsutdinovich Zaurbekov; Arbi Akhamdievich Shaipov; Magomed Makhmudovich Labazanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the growing interest in renewable energy, where geothermal waters have special significance. The prospects for using geothermal waters are proved by their environmental benefits. However, the economic aspects of exploitation need to be studied. The main aim of the study is the feasibility study of the project for constructing a geothermal plant with a circulating heat extraction scheme on the basis of the Khankala geothermal waters deposit of the Chechen Republic. The methods used in the study: calculation of the economic parameters of investment attractiveness of the project for constructing the Khankala geothermal plant based on discounted cash flows on the following standard criteria: net present value, internal rate of return, payback period and discounted payback period; study of the possible risks of the Khankala geothermal waters deposit development and ways to minimize them; comparative analysis with gas boiler, worldwide experience of geothermal projects implementation, including consideration of government incentives to stimulate the use of geothermal waters. The results. The authors have proved the prospects for geothermal waters use in the Chechen Republic, and calculated the indicators of investment attractiveness of the project for constructing the Khankala geothermal plant and similar stations within the study area, confirming the economic feasibility of using this resource. The paper considers the advantages of the development of geothermal waters of Chechnya, as well as the main risks associated with geothermal projects, and the ways to minimize them. The forecast for the possible substitution of fossil fuels by using geothermal waters of the study area is introduced. The recommendations to promote the development of geothermal energy in Russia are given.